Assess Spatial Equity Considering the Similarity Between GIS-Based Supply and Demand Maps: A New Framework with Case Study in Beijing - Xiatong Hao; Xiaojian Hu; Ke Zhang; Qian Chen (ISPRS International Journal of Geo-Information)
Spatial equity is a critical issue that the supply allocation should align with the level of demand, enabling all community members to equally benefit from the city’s resources and opportunities, yet commonly used assessment methods have inherent limitations. This study proposes a new framework to assess spatial equity based on the evaluation of similarity between GIS-based supply and demand maps and provides a simplified case study that assesses public transportation services across the area inside the Sixth Ring Road of Beijing to facilitate the comprehension of this framework. The results show that while services in this region are relatively spatially equitable, significant spatial inequity remains in certain areas, where targeted policy recommendations are put forward such as promoting innovative transportation solutions and redistributing excessive demand to less congested facilities. The application prospects and future development directions of the proposed framework are thoroughly discussed. This framework stands out for its ease of comprehension, visualization, and general applicability. Specifically, it is capable of identifying areas with severe inequity, thus contributing to the establishment of targeted intervention measures to mitigate spatial inequity.